Implementasi Pembelajaran Berdiferensiasi Dalam Kurikulum Merdeka Terhadap Keragaman Peserta Didik di TK Negeri Pembina Salatiga - Widodo, Widodo; Aviyanti, Choirunisa Auliya; Wulandari, Cahyorini; Nastiti, Deinta Putri; Ningrum, Fatwati Fuani Cahya (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2024)
Differentiated learning is a learning concept that can be applied in schools with a diversity of students. In this differentiated learning, the role of the teacher as a facilitator is very important in an effort to meet the diverse learning needs of students. By knowing the characteristics of students at the beginning, teachers can become a reference in preparing learning plans. The aim of this research is to describe and explore the implementation of differentiated learning as one of the teacher's efforts to meet the learning needs of students with a diversity of students within the framework of an independent curriculum. Through this differentiated learning, the teacher first carries out an initial assessment as a form of finding out the characteristics of the students. So, then the teacher can prepare an appropriate learning plan to achieve the determined learning objectives. The components of differentiation learning are content differentiation, process differentiation, product differentiation.